PERAN KOPERASI DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT NELAYAN: PERSPEKTIF MODAL KERJA - Fiqih Putra Arifandy; Norsain Norsain; Imam Darul Firmansyah (Jurnal Akademi Akuntansi, 2020)
Fishers are faced with various kinds of problems. In this case, Koperasi is expected to be something that can easily adjust its role to the needs of the fishing and coastal communities. This study aims to analyze the role of Koperasi in improving the economy of fishing communities in Sumenep Regency. This study uses qualitative data that emphasizes the meaning with qualitative data analysis techniques consisting of reduction, data presentation, conclusion, and verification. The results of this study indicate that the Koperasi has a significant role in improving the welfare of the community, especially members of the Koperasi so that it will ultimately have an impact on improving the economy in Padangdangan Village, Pasongsongan District. The real role of Koperasi in Padangdangan Village, Pasongsongan District is to build community awareness in Koperasi, as a provider of working capital needs through savings and loan activities, as a means of supporting fishing activities in the form of fishing gear and thermo king tools, as a facilitator in establishing partnerships and Koperasi with parties outside, as well as a medium to increase fishermen's income.